Language Learning Disabilities: How Can I Help My Students with Dyslexia? - Apriani, Eka; Supardan, Dadan (ENGLISH FRANCA : Academic Journal of English Language and Education, 2018)
Abstract This paper showed the language learning method in teaching disabilities students with dyslexia problem. In this article the main focus is how to teach the dyslexia students in reading skill. Furthermore, in this study also explain the causes of dyslexia which are neurological and cognitive factor. Beside of that, the characteristics of children with dyslexia divided into two stages: early childhood (preschool or kindergarten, Grade 1-3, and Grade 4-8) and middle childhood with dyslexia (High school, college, and adult). And the last teacher has important role in teaching for the students with reading disabilities and difficulties (dyslexia). Teacher can guide the student in learning, give them an interesting activities by using good strategy. Keyword: Reading Skill, Dyslexia, and Language Learning.